Finite Element Simulation and Performance Test of Loading and Mixing Characteristics of Self-Propelled Total Mixed Ration Mixer - Fuyang Tian; Yuhua Chen; Zhanhua Song; Yinfa Yan; Li Fade; Zhonghua Wang; Benhai Xiong (Journal of Engineering)
Simulation analysis and parameter optimization are performed for the loading and mixing devices of a self-propelled total mixed ration mixer. To reveal the three-dimensional movement of silage material under the action of the loading cutter roller, the latter is modeled using SolidWorks software. ANSYS/LS-DYNA software is used to simulate the process of silage cutting, which is modeled using smoothed particle hydrodynamics coupled with the finite element method. The cutting force and power consumption are simulated, and the behavior of the equivalent strain of the silage is determined. The results showed that silage was broken up mainly by extrusion and shear force due to the loading cutter roller. The power consumption according to the simulation is consistent with the value from an empirical formula, confirming the validity of the proposed modeling method. To study the mixing performance and obtain the optimum parameters of the mixing device, the Hertz–Mindlin model is used for the interaction between material particles and mixing device. A three-factor, five-level method is used to optimize the mixing performance. Material-mixing time, loading rate, and auger speed are chosen as experimental factors and mixed uniformity as an evaluation index. It is found that auger speed and material mixing time have significant effects on mixing uniformity. These results provide reference values allowing the analysis of the crushing of silage and selection of the optimum parameters for mixing performance.